2021
DOI: 10.3390/en14123387
|View full text |Cite
|
Sign up to set email alerts
|

Descending Modal Transition Dynamics in a Large Eddy Simulation of a Rotating Detonation Rocket Engine

Abstract: Rotating detonation rocket engines (RDREs) exhibit various unsteady phenomena, including modal transitions, that significantly affect their operation, performance and stability. The dynamics of the detonation waves are studied during a descending modal transition (DMT) where four co-rotating detonations waves decrease to three in a gaseous methane-oxygen RDRE. Detonation wave tracking is applied to capture, visualize and analyze unsteady, 3D detonation wave dynamics data within the combustion chamber of the RD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Fig. 2 [4] is a produced and tested strident rocket engine which shares the similar geometric and theoretical concept as the SABRE, but had been designed only for cold flow testing [10].…”
Section: Prospectsmentioning
confidence: 99%
“…Fig. 2 [4] is a produced and tested strident rocket engine which shares the similar geometric and theoretical concept as the SABRE, but had been designed only for cold flow testing [10].…”
Section: Prospectsmentioning
confidence: 99%
“…A detonation wave is a kind of supersonic combustion wave that consists of shock waves driven by energy release from closely coupled chemical reactions, which has broad application prospects in the field of aerospace propulsion technology [1][2][3][4][5]. As one of the innovative propulsion devices, a pulse detonation engine (PDE) generates thrust by using detonation waves and has attracted great attention due to its simple structure and high thermodynamic cycle efficiency [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism and process of mode switching is difficult to be revealed by experiments. Batista et al carried out simulation to explain the mechanism of Descending Modal Transition(DMT) process [24]. They found that critical reactant mixing height is an indicator of detonation wave viability.…”
Section: Introductionmentioning
confidence: 99%